2019
DOI: 10.1017/s1471068418000480
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic DL Reasoning with Pinpointing Formulas: A Prolog-based Approach

Abstract: When modeling real-world domains, we have to deal with information that is incomplete or that comes from sources with different trust levels. This motivates the need for managing uncertainty in the Semantic Web. To this purpose, we introduced a probabilistic semantics, named DISPONTE, in order to combine description logics (DLs) with probability theory. The probability of a query can be then computed from the set of its explanations by building a Binary Decision Diagram (BDD). The set of explanations can be fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…We are currently working on a probabilistic extension of HKBs with function symbols, inspired by Sato's distribution semantics [14], which will be based on the iterated fixpoint operator defined in this paper. The probabilistic language of probabilistic HKB FS will be also equipped with a query answering system, in the style of what we did in TRILL [17,16] and PITA [13], comparing our system with that of Knorr and colleagues [9].…”
Section: Discussionmentioning
confidence: 99%
“…We are currently working on a probabilistic extension of HKBs with function symbols, inspired by Sato's distribution semantics [14], which will be based on the iterated fixpoint operator defined in this paper. The probabilistic language of probabilistic HKB FS will be also equipped with a query answering system, in the style of what we did in TRILL [17,16] and PITA [13], comparing our system with that of Knorr and colleagues [9].…”
Section: Discussionmentioning
confidence: 99%
“…Probabilistic systems that can perform inference under DISPONTE are BUNDLE [12,13] and the TRILL framework. The first one is implemented in Java and it can exploit several non-probabilistic reasoners, the latter is a framework, written in Prolog, which contains three reasoners, namely, (i) TRILL [14,10], able to collect the set of all justifications and compute the probability of queries, (ii) TRILL [14,10], which implements in Prolog the tableau algorithm defined by Baader and Peñaloza [15,16] for returning the pinpoint-ing formula instead of the set of justifications, and (iii) TOR-NADO [17], which is similar to TRILL but represents the pinpointing formula in a way that can be directly used to compute the probability of the query.…”
Section: Introductionmentioning
confidence: 99%
“…The reasoners contained in the TRILL framework exploit Prolog's backtracking facilities for performing the search. In addition, the experiments performed by [17] showed that a Prolog implementation of the tableau algorithm can achieve competitive or even better results than other state-of-the-art (non-)probabilistic reasoners.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, in [27,36] we introduced the DISPONTE semantics, which applies the distribution semantics [30] to DLs. Examples of systems that perform probabilistic logic inference under DISPONTE are BUNDLE [27,28,36], and TRILL [38,36,37]. The former is implemented in Java, the latter in Prolog.…”
Section: Introductionmentioning
confidence: 99%
“…In this chapter, we illustrate the state of the art of the BUNDLE framework. In particular, we present a newer version of BUNDLE which also interfaces with the probabilistic reasoners of the TRILL system, namely: (i) TRILL [38,36], which solves the justification finding problem, (ii) TRILL P [38,36], which returns the pinpointing formula using the approach defined in [2,3], and (iii) TOR-NADO [37], which, similarly to TRILL P , returns the pinpointing formula, but the formula is represented in a way that can be directly used to compute the probability. In this way, the user can run probabilistic queries in a uniform way by using the preferred reasoner.…”
Section: Introductionmentioning
confidence: 99%